(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
This research is aimed at analyzing, in the light of Semiotics, the communicability of the whatsapp application. It is a basic research, with a qualitative approach and experimental technique, which made use of the Semiotic Inspection Method to evaluate the transmission of the metalanguage of the whatsapp interaction interfaces designer. The target audience is made up of elderly users between 65 and 85 years old. As a result, of the four activities in the scenario established for the application of the Semiotic Inspection Method, it is considered that three present possible breaking points in the communicability of whatsapp with the elderly user, possibly because it does not allow for the assertive semiosis of the signs. This heralds the possibility of reflection by designers regarding the arrangement of signs in the application, as the elderly are massive in Brazilian society.